Marketability and sustainability of Klikdito.ph online buying and selling website in the Philippines - Candelaria, Harold B. (Technology Management Center, 2014)
As a new entrant in the Philippine online marketspace providing a single platform for online buying and selling, Klikdito.ph understands the challenges ahead in competing with well-established brands and competitors. The website was developed based from the concept of the existing industry leaders in online buying and selling platform - Sulit.com.ph and Ayosdito.ph which makes Klikdito.ph it a mere copy that offers the same service for advertising. Nevertheless, the website was hopes to capture a portion of the market by providing a fresh look platform with a fast, easy and secure feature offered to ordinary individuals and at the same time establish a brand of its own through the use of effective marketing strategy implementation. One major issue concerning Klikdito.ph is the marketability and sustainability of the website for longer term considering the saturation of the online industry where new business ideas and concepts are sprouting everywhere. With the help of this research, the implementation of the strategy and solution contribute in positioning the website in a way that it will continue to operate and flourish even the emergence of many competitions surrounding the field of online buying and selling industry. Improving the online presence of the website is one aspect that must be given focus based on the implemented strategy in order to continue in capturing certain niche of the market. Nonetheless, continuous refinement of the strategy is crucial in order to have a steady stream for website traffic which is the source of potential revenue for the website. Understanding the current state of the business through SWOT analysis helped the management team to have a better picture on how certain strategy and solution will be applied. Knowing on which aspects and external entities that have potential impact allows the management to prepare and anticipate the necessary actions to be implemented for future improvements. Using common methodology of quantitative research the management team was able to understand on which solution and strategy yield better results through comparative statistic. However, online limitation of the research method is it only capture figures gathered from free online tools where information are limited and may not be accurate on the actual business standpoint as baseline for comparison. The use of common framework and simple concept effectively guide the research flow of implementing different solution and strategy for marketing the website. Translating the classic brick and mortar concept and the process of marketing the business to social media, Klikdito.ph was able to apply solutions that essentially improve its online presence. The solution showed that the most effective tool for marketing is actually through the use of the Internet itself compared with other offline marketing solutions. Using online tools such as paid advertising from Facebook the website dramatically increased social network presence to more than 2500 percent which is a very huge figure. Similarly, Google paid advertising consistently maintained its market reach to 1,500 visitors on a weekly basis. The increased in traffic was a key driver that can potentially translate into revenue. However, improving website traffic does not essentially guarantee long term success for Klikdito.ph. Addressing other key issues that pertains to business capabilities such as business registration which is critical for any business startups and resources management to sustain business operation should not be neglected by the management team. Klikdito.ph must also understand the benefits of improving the business from its core operation and not just improving the website traffic. Based on this research Klikdito.ph requires further improvement that later on could bring longer benefits if given with the right attention. Refining not just Klikdito.ph website but also the entire delivery of service will make the business sustain the growing market competition in online buying and selling industry. It is recommended that; The Klikdito.ph must improve the core business by securing the right permit of business registration; applying for patent protection for their brand and trademarks; creating a definitive mission and vision for the business; and, drafting a clear agreements through contract among business owners. Improve the management capabilities by employing additional people that will assume the right roles and responsibilities within the business. Allocate a consistent budget that is distributed in all areas of the business such as 50 percent on marketing and another 50 percent on operation. Thus, ensuring that all sides of the business are covered and no other areas are neglected. Additionally, the management should look for additional source of funds through partnership as a form of diversification to limit the reliance on member's personal source of income.